A nationwide study of SLE in Japanese identified subgroups of patients with clear signs patterns and associations between signs and age or sex. (November 2014) - Terao, C; Yamada, R; Mimori, T; Yamamoto, K; Sumida, T
We performed a nationwide study to determine the distributions of the signs and clinical markers of systemic lupus erythematosus (SLE) and identify any patterns in their distributions to allow patient subclassification. We obtained 256, 999 patient-year records describing the disease status of SLE patients from 2003 to 2010. Of these, 14, 779 involved patients diagnosed within the last year, and 242, 220 involved patients being followed up. Along with basic descriptive statistics, we analyzed the effects of sex, age and disease duration on the frequencies of signs in the first year and follow-up years. The patients and major signs were clustered using the Ward method. The female patients were younger at onset. Renal involvement and discoid eczema were more frequent in males, whereas arthritis, photosensitivity and cytopenia were less. Autoantibody production and malar rash were positively associated with young age, and serositis and arthritis were negatively associated. Photosensitivity was positively associated with a long disease duration, and autoantibody production, serositis and cytopenia were negatively associated. The SLE patients were clustered into subgroups, as were the major signs. We identified differences in SLE clinical features according to sex, age and disease duration. Subgroups of SLE patients and the major signs of SLE exist.